George Frideric Handel - Ludwig, Charles; Nang ChanYeema (Milford, MI USA Mott Media, Inc., 1987)
A biography of the composer of more than forty operas, nineteen oratorios, including the famous "Messiah," and hundreds of other vocal and instrumental works.
Keywords: Biography